An In Vitro Synergistic Interaction of Combinations of Thymus glabrescens Essential Oil and Its Main Constituents with Chloramphenicol - Budimir S. Ilić; Branislava D. Kocić; Vojislav M. Ćirić; Olga G. Cvetković; Dragoljub L. Miladinović (The Scientific World Journal)
The chemical composition and antibacterial activity of Thymus glabrescens Willd. (Lamiaceae) essential oil were examined, as well as the association between it and chloramphenicol. The antibacterial activities of geraniol and thymol, the main constituents of T. glabrescens oil, individually and in combination with chloramphenicol, were also determined. The interactions of the essential oil, geraniol, and thymol with chloramphenicol toward five selected strains were evaluated using the microdilution checkerboard assay in combination with chemometric methods. Oxygenated monoterpenes were the most abundant compound class in the oil, with geraniol (22.33%) as the major compound. The essential oil exhibited in vitro antibacterial activity against all tested bacterial strains, but the activities were lower than those of the standard antibiotic and thymol. A combination of  T. glabrescens oil and chloramphenicol produced a strong synergistic interaction (FIC indices in the range 0.21–0.87) and a substantial reduction of the MIC value of chloramphenicol, thus minimizing its adverse side effects. The combinations geraniol-chloramphenicol and thymol-chloramphenicol produced synergistic interaction to a greater extent, compared with essential oil-chloramphenicol association, which may indicate that the activity of the thyme oil could be attributed to the presence of significant concentrations of geraniol and thymol.